Effect modification of ambient particle mortality by radon: A time series analysis in 108 U.S. cities. (4th March 2019) - Blomberg, Annelise J.; Coull, Brent A.; Jhun, Iny; Vieira, Carolina L.Z.; Zanobetti, Antonella; Garshick, Eric; Schwartz, Joel; Koutrakis, Petros
ABSTRACT: Numerous studies have reported a positive association between ambient fine particles and daily mortality, but little is known about the particle properties or environmental factors that may contribute to these effects. This study assessed potential modification of radon on PM2.5 (particulate matter with an aerodynamic diameter <2.5 μm)-associated daily mortality in 108 U.S. cities using a two-stage statistical approach. First, city- and season-specific PM2.5 mortality risks were estimated using over-dispersed Poisson regression models. These PM2.5 effect estimates were then regressed against mean city-level residential radon concentrations to estimate overall PM2.5 effects and potential modification by radon. Radon exposure estimates based on measured short-term basement concentrations and modeled long-term living-area concentrations were both assessed. Exposure to PM2.5 was associated with total, cardiovascular, and respiratory mortality in both the spring and the fall. In addition, higher mean city-level radon concentrations increased PM2.5 -associated mortality in the spring and fall. For example, a 10 µg/m 3 increase in PM2.5 in the spring at the 10th percentile of city-averaged short-term radon concentrations (21.1 Bq/m 3 ) was associated with a 1.92% increase in total mortality (95% CI: 1.29, 2.55), whereas the same PM2.5 exposure at the 90th radon percentile (234.2 Bq/m 3 ) was associated with a 3.73% increase in total mortality (95% CI: 2.87, 4.59). Results were robust to adjustment for spatial confounders, including average planetary boundary height, population age, percent poverty and tobacco use. While additional research is necessary, this study suggests that radon enhances PM2.5 mortality. This is of significant regulatory importance, as effective regulation should consider the increased risk for particle mortality in cities with higher radon levels. Implications : In this large national study, city-averaged indoor radon concentration was a significant effect modifier of PM2.5 -associated total, cardiovascular, and respiratory mortality risk in the spring and fall. These results suggest that radon may enhance PM2.5 -associated mortality. In addition, local radon concentrations partially explain the significant variability in PM2.5 effect estimates across U.S. cities, noted in this and previous studies. Although the concept of PM as a vector for radon progeny is feasible, additional research is needed on the noncancer health effects of radon and its potential interaction with PM. Future air quality regulations may need to consider the increased risk for particle mortality in cities with higher radon levels.